Facial conversion of secondary phosphine oxides R1R2P(O)H to chlorophosphines R1R2PCl by acetyl chloride. Issue 10 (5th March 2020) - Zhang, Jian-Qiu; Yang, Shangdong; Han, Li-Biao
Graphical abstract: Highlights: Secondary phosphine oxides to chlorophosphines. Using AcCl instead of PCl3. High yields, easy purification. Abstract: A practically useful protocol for the reductive transformation of secondary phosphine oxides R 1 R 2 P(O)H to chlorophosphines R 1 R 2 PCl using acetyl chloride was disclosed. Various secondary phosphine oxides could be readily reduced to the corresponding chlorophosphines in high yields under mild conditions.